FRI0420 Health Related Quality of Life in Lupus Differs by How Patients Perceive their Health and How Often They Experience Flares: Findings from a Cross-Sectional Online Survey in the United States. (9th June 2015) - Daly, R.P.; Al Sawah, S.; Foster, S.; Naegeli, A.; Benjamin, K.; Doll, H.; Bond, G.; Moshkovich, O.; Alarcόn, G.
Abstract : Background: Lupus affects patients' health related quality of life (HRQoL). Objectives: The aim of this study was to evaluate, in a sample of patients with lupus, HRQoL and how it varies according to patients' perception of their health and their flare frequency. Methods: An online cross-sectional survey of English-speaking respondents aged ≥18 years with self-reported diagnosis of lupus was conducted across the US in partnership with the Lupus Foundation of America between February and March 2014. Demographic, clinical, and HRQoL information was obtained. HRQoL was measured by the LupusPRO 1, a validated lupus-specific QoL instrument consisting of 2 constructs (HRQoL and non-HRQoL) and 12 domains (HRQoL domains: lupus symptoms, cognition, lupus medications, procreation, physical health, pain-vitality, emotional health, and body image; non-HRQoL domains: desires-goals, social support, coping, and satisfaction with medical care). All constructs and domains scores range from 0 to 100 (with 100 indicating the most satisfaction). Health status and frequency and severity of flares were assessed as perceived by patients. Results: Of the 827 patient respondents, 97.5% were females, 85.3% were white, 13.5% were Black, and 13.7% were Hispanic. A total of 66.3% perceived their health as either Fair or Poor, whereas 9.1% perceived it as either Very Good or Excellent. Recalling the past 4 weeks when completing the survey, 42.8% reported experiencing a lupus flare Most of the Time or All of the Time and 22.9% reported A Little of the Time or None of the Time. Overall, mean HRQoL (45.9; SD, 19.6) and non-HRQoL (54.0; SD, 17.1) scores implied a detrimental effect of lupus on QoL. The pain-vitality domain had the lowest mean score (32.0; SD, 24.1), indicating that pain and fatigue had the greatest relative impact on overall HRQoL, with patients affected, on average, Most of the Time. The highest single domain score was 63 (for coping), indicating that even in the least impacted domain patients were still being affected, on average, A Little of the Time or Some of the Time. Relating HRQoL to perceived health, HRQoL scores decreased linearly the poorer the patients' perceived health – from (67.5; SD, 21.3) in the 9.1% of those perceiving their health as Excellent or Very Good to (29.8; SD, 15.3) in the 19.7% perceiving their health as Poor (p<0.001). Similarly, in terms of flare frequency, HRQoL scores decreased linearly the greater the reported flare frequency – from (72.6; SD, 18.6) in those reporting flares None of the Time to (27.3; SD, 14.8) in those reporting flares Almost all of the Time/Almost Every Day" (p<0.001). Conclusions: HRQoL is significantly compromised in patients with lupus and is further impacted by how patients perceive their health and how often patients perceive they are experiencing flares. Better understanding of the main drivers of reduced HRQoL in this patient population will be important for future targeted interventions and treatment. References: Jolly M, Pickard AS, Block JA, et al. Disease-specific patient reported outcome tools for systemic lupus erythematosus. Sem Arthritis Rheum 2012;42:56-65. Disclosure of Interest: R. P. Daly: None declared, S. Al Sawah Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, S. Foster Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, A. Naegeli Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, K. Benjamin: None declared, H. Doll: None declared, G. Bond: None declared, O. Moshkovich: None declared, G. Alarcόn: None declared